Advanced Roof Cutting and Pressure Relief Technology and Application of Mining Roadway - Mi, Chao (International Journal of Natural Resources and Environmental Studies, 2025)
In order to solve the problems of complex advanced support of the mining roadway, high labor intensity, poor control effect of the surrounding rock of the roadway, and the impact of the mining efficiency of the working face during the mining period of the 12203 working face of Xinzheng Coal and Power Co., Ltd., the control technology of the surrounding rock of the mining roadway in the advanced area of the mining roadway was proposed. The numerical simulation data show that the peak value of the advanced support pressure is located 8.24m in front of the working and the peak vertical stress is 21.63MPa in the non-roofing scheme, and the peak value of the advanced support pressure is located 8.64m in front of the working roadway, and the peak stress increases slightly to 21.85MPa, so as to realize the transfer of the peak value of the advanced support pressure to the deep part of the coal and rock mass. The stress concentration area of the shallow surrounding rock in the roof cutting scheme is transferred to the deep part, so that the shallow surrounding rock of the roadway is in a relatively low stress state, which significantly improves the stress environment in the advanced area of the mining roadway and provides favorable conditions for the stability control of the roadway.